2021
DOI: 10.22438/jeb/42/5/mrn-1894
|View full text |Cite
|
Sign up to set email alerts
|

Impact and prospects of water conservation on fish habitat and advances of ecobiology operation in Yangtze River, China: A review

Abstract: Yangtze River, the longest river in Asia, provides 40 percent of freshwater in China and plays an important role in ecological biodiversity. However, this ecosystem has been deteriorated by the continuously construction of reservoirs and hydropower stations. Many investigations have been carried for the biodiversity, hydrological indicators, and species distribution along Yangtze River caused by dam construction. As a result, the ecological operation has been gradually applied to mitigate the negative effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 57 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…Therefore, the use of the measured indicators, have allowed us to identify responses at the population level that indicate that the charal population, is at extreme risk of being extirpated from the study area. Taking this into consideration, it is a priority to make changes and adjustments to the management plan of this site, as well as to the current regulations, at the same time a call is made for the involvement of all stakeholders that have an influence on the management of the habitat and the resources still present, as well as continuing monitoring programs and proposing alternatives for the repopulation of the species in less impacted areas (Zhang, et al, 2021, Latournerié-Cervera et al, 2021a.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the use of the measured indicators, have allowed us to identify responses at the population level that indicate that the charal population, is at extreme risk of being extirpated from the study area. Taking this into consideration, it is a priority to make changes and adjustments to the management plan of this site, as well as to the current regulations, at the same time a call is made for the involvement of all stakeholders that have an influence on the management of the habitat and the resources still present, as well as continuing monitoring programs and proposing alternatives for the repopulation of the species in less impacted areas (Zhang, et al, 2021, Latournerié-Cervera et al, 2021a.…”
Section: Discussionmentioning
confidence: 99%
“…River hydrological processes are the primary drivers of river ecosystems, and their natural regimes have been adopted as paradigms for protecting and restoring ecological integrity. River hydrologic variability directly affects aquatic species and abundance 1 , 2 . Fish are essential aquatic biological resources that are sensitive to changes in flow regime 3 , 4 , especially during spawning and rearing.…”
Section: Introductionmentioning
confidence: 99%
“…Peng, et al 11 showed that the reduction in peak flows caused by the dams would result in the failure of downstream fish to spawn. Given this challenge, quantitative assessment of changes in characteristic hydrologic parameters 16 and analysis of ecological flows required by the fish spawning process 2 , 11 , 17 are essential for river habitat restoration.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most important ecosystems, lake could provide various valuable ecological services for local economic and social development, including drinking water, agriculture, fisheries, climate regulation, and flooding control, and also serve for biodiversity providing aesthetic and economic benefits (Dearing et al 2012;Liu et al 2012;Laj et al 2022). In recent decades, a large number of artificial lakes have been formed along rivers due to the construction of dams, which were aimed at using water energy resources for power generation, navigation, and irrigation (Zhang et al 2021;Serafim-Júnior et al 2016;Etourneau et al 2013). However, urban artificial lakes which were used as urban water resources and characterized by stagnant water bodies, fragile ecosystems, and irregular shapes were more easily affected by interference and rapid urbanization from human activities (Yang et al 2021;Wang et al 2013).…”
Section: Introductionmentioning
confidence: 99%